Nedfarten til dødsriget - Balling, Jakob (Grundtvig-Studier, 2001)
The Descent into Hell By Jakob Balling This article - originally a paper, read at the Grundtvig Academy’s conference on Grundtvig and the Figurative Arts in November 2000 - presents an interpretative sketch of the uses made of the descensus motif from the beginning, via the ‘Gospel of Nicodemus’, ancient and medieval liturgical and liturgico-dramatic texts, and Luther, to Grundtvig. Throughout, the main emphasis of the discussion is laid on the way in which the texts express and expound the notions of coherence between creation and salvation and of past history being actualized or re-enacted in the present. - By way of conclusion, the story is, consequently, maintained to communicate a vast complex of central tenets of the Christian faith.